Front-office/back-office configurations and operational performance in complex health services. (March 2014) - Gemmel, Paul; van Steenis, Thomas; Meijboom, Bert
Abstract Background: Acquired brain injury (ABI) occurs from various causes at different ages and leads to many different types of healthcare needs. Several Dutch ABI-networks installed a local co-ordination and contact point (CCP) which functions as a central and easily accessible service for people to consult when they have questions related to ABI. Goals: To explore the relationship between front/back office design and operational performance by investigating the particular enquiry service provided by different CCPs for people affected by an ABI. Methods: In-depth interviews with 14 FO/BO employees from three case organizations, complemented with information from desk research and three one-day field visits. Results: The CCPs applied different FO/BO configurations in terms of customer contact and in terms of grouping of front and/or back office activities into tasks for one employee. Discussion: It is the complexity of the enquiry that determines which approach is more appropriate. For complex enquiries, the level of decoupling is high in all CCPs. This allows multiple experts to be involved in the process. For regular enquiries, CCPs have a choice: either working in the same way as in the complex enquiries or coupling FO/BO activities to be able to serve clients faster and without handovers.